A role of reactive oxygen species in apoptotic activation of volume-sensitive Cl(-) channel - Shimizu, Takahiro (National Academy of Sciences, 2004)
Apoptotic volume decrease is a pivotal event triggering a cell to undergo apoptosis and is induced by ionic effluxes resulting mainly from increased K(+) and Cl(-) conductances. Here, we demonstrate that in human epithelia HeLa cells both mitochondrion- and death receptor-mediated apoptosis inducers [staurosporine and Fas ligand or tumor necrosis factor (TNF)-α] rapidly activate Cl(-) currents that show properties phenotypical of volume-sensitive outwardly rectifying Cl(-) channel currents, including outward rectification, voltage-dependent inactivation gating at large positive potentials, inhibition by osmotic shrinkage, sensitivity to classic Cl(-) channel blockers, and dependence on cytosolic ATP. Staurosporine, but not Fas ligand or TNF-α, rapidly (within 30 min) increased the intracellular level of reactive oxygen species (ROS). A ROS scavenger and an NAD(P)H oxidase inhibitor blocked the current activation by staurosporine but not by Fas ligand or TNF-α. A ROS scavenger also inhibited apoptotic volume decrease, caspase-3 activation, and apoptotic cell death induced by staurosporine. Thus, it is concluded that an apoptosis-triggering anion conductance is carried by the volume-sensitive outwardly rectifying Cl(-) channel and that the channel activation on apoptotic stimulation with staurosporine, but not with Fas ligand or TNF-α, is mediated by ROS.